Stem Cell Injection for Complex Refractory Perianal Fistulas in Crohn's Disease: A Single Center Initial Experience - Colombo, Francesco; Cammarata, Francesco; Baldi, Caterina; Rizzetto, Francesco; Bondurri, Andrea; Carmagnola, Stefania; Gridavilla, Daniele; Maconi, Giovanni; Ardizzone, Sandro; Danelli, Piergiorgio (Frontiers in Surgery, 2022)
From 30 to 70% of Crohn’s disease (CD) patients may develop perianal fistulas during their lifetime. The medical and surgical management of this complication is challenging, and its treatment still gives unsatisfactory results. However recent studies on adipose-derived mesenchymal stem cells have proven their anti-inflammatory and immuno-modulatory potential, representing a new promising tool in the treatment of such stubborn disease. We report our initial experience of three patients with recurrent perianal CD treated with local infiltration of stem cells Darvadstrocell (Alofisel). All patients had a long history of perianal disease, refractory to multiple medical and surgical treatments. The preoperative work-up included transperineal ultrasound (TP-US), pelvic magnetic resonance imaging (MRI) and colonoscopy that ruled out an active proctitis in all patients. The post-treatment follow-up included clinical assessment at 1, 3 and 6 months, with repeated MRI and TP-US at 6 months. At 6 months 2 patients had a clinical response, despite radiological persistence of the fistulous tracks, while one patient presented perianal fistula recurrence complicated by a perianal abscess. Although our experience is limited on 3 patients and a short follow-up, our results confirm that Darvadstrocel injection is a safe procedure, with a good clinical response in most patients, but apparently without effect on the anatomical modification of the fistulas tracks. Long-term results, with rigorous assessment of anatomical lesions are still needed to support the promising data of the literature.